2016
DOI: 10.3389/fneur.2016.00145
|View full text |Cite
|
Sign up to set email alerts
|

Does Side of Onset Influence the Pattern of Cerebral Atrophy in Parkinson’s Disease?

Abstract: BackgroundImaging studies have revealed widespread neurodegeneration in Parkinson’s disease (PD), but only a few considered the issue of asymmetrical clinical presentations.ObjectiveTo investigate if the side of onset influences the pattern of gray matter (GM) atrophy in PD.MethodsSixty patients (57.87 ± 10.27 years) diagnosed with idiopathic PD according to the U.K. Brain Bank criteria, 26 with right-sided disease onset (RDO) and 34 with left-sided disease onset (LDO), were compared to 80 healthy controls (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our total PD sample demonstrated smaller GMV in the left hemisphere in stages 1 + 2, which was independent of the MAH DaT . This finding accords with previous studies that found left‐hemisphere‐dominant atrophy, which was not influenced by the dominant side of motor symptoms 53,54 . It is tempting to speculate that the left hemisphere is particularly susceptible to atrophy, whereby gray matter changes in the left hemisphere may be more pronounced specifically in the early stages of the disease 54‐57 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our total PD sample demonstrated smaller GMV in the left hemisphere in stages 1 + 2, which was independent of the MAH DaT . This finding accords with previous studies that found left‐hemisphere‐dominant atrophy, which was not influenced by the dominant side of motor symptoms 53,54 . It is tempting to speculate that the left hemisphere is particularly susceptible to atrophy, whereby gray matter changes in the left hemisphere may be more pronounced specifically in the early stages of the disease 54‐57 .…”
Section: Discussionsupporting
confidence: 91%
“…This finding accords with previous studies that found left-hemispheredominant atrophy, which was not influenced by the dominant side of motor symptoms. 53,54 It is tempting to speculate that the left hemisphere is particularly susceptible to atrophy, whereby gray matter changes in the left hemisphere may be more pronounced specifically in the early stages of the disease. [54][55][56][57] Although there is also contradictory evidence to this account, it seems that this vulnerability of the left hemisphere is also shared by other neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 75.64% of patients had an upper limb onset, which was in line with the literature [24] . Imaging studies reported the side of onset might in uence the pattern of cerebral atrophy in PD [25] , however, whether the side of onset affects the progression of PD had not been reported. In agreement with another literature, our study showed that mixed subtype was regarded as the commonest type [26,27] , and the number of patients with akinetic-rigid subtype who were at ES was the smallest, while the results were reversed in mixed subtype patients at AS (Table 1).…”
Section: Overall Characteristics Of 193 Pd Patientsmentioning
confidence: 99%
“…Former studies suggested that the compensatory mechanisms in the dominant hemisphere of brain may be an underlying explanation [7,8]. Neuroimaging studies have found that PD patients with different onset or more affected sides showed distinct image features [7,10], suggesting differences in the degenerative patterns between two hemispheres during the progression of the disease. The corpus callosum (CC) is the largest ber bundle that connects two hemispheres and projects to different functional brain areas.…”
Section: Introductionmentioning
confidence: 99%